Teori Konstruktivistik dalam Pembelajaran PAI: YPI Al-Barokah Gondanglegi - Syuaib, Muhammad; Romadhon, Mochamad Rizqy; Zaironi, Muhammad (TSAQOFAH, 2026)
Education is a fundamental foundation for shaping human character and patterns of thought, thereby requiring learning approaches that not only transmit knowledge but also encourage students to actively construct their own understanding. One relevant approach is constructivist theory, which emphasizes that knowledge is constructed through direct experience and social interaction. This study aimed to understand the application of constructivist theory in Islamic Religious Education (PAI) learning at Al-Barokah Gondanglegi. A descriptive qualitative approach with a field research design was employed, enabling the researcher to observe learning dynamics in a natural setting, including patterns of interaction between teachers and students. The findings show that the application of constructivist theory in PAI learning encourages students to connect new knowledge with prior experiences, making learning more meaningful while simultaneously stimulating critical thinking skills, creativity, and active participation in the learning process. The study affirms that constructivist theory plays an important role as a pedagogical foundation in PAI learning, with implications for strengthening teachers’ competence in designing contextual and learner-centred learning experiences.